Survey on Energy Efficient Routing Protocols by Clustering and Load balancing in Wireless Sensor Networks - S.Shetty, Bharati.; ., Suresha (International Journal of Engineering and Technology, 2018)
Wireless Sensor Network (WSN) is consisting of nodes which deployed to sense the physical environment. In WSN there is excessive growth in performance evaluation and analysis techniques, because of fast development in Information and Communication Technologies (ICT). The main resource problem in WSN is the energy of sensor nodes. There is need of routing protocol which consumes less energy during communication. A reliable and robust routing protocol which limits the excess energy consumed by nodes during forwarding and receiving messages results in energy efficiency protocol. This survey work provides the advantages, drawbacks and comparison of five energy efficient routing protocols.Â Â